Respons Imun Puyuh (Coturnix coturnix Japonica) Dewasa yang Mendapat Ekstrak Daun Singkong dalam Mengatasi Dampak Cekaman Panas (IMMUNE RESPONSE OF ADULT QUAILS (COTURNIX COTURNIX JAPONICA) TREATED WITH CASSAVA LEAF EXTRACT TO OVERCOME HEAT STRESS) - Santoso, Koekoeh; Widyadhari, Anindita Sista; Poetri, Okti Nadia; Jumadin, La (Jurnal Veteriner; Vol 20 No 4 (2019)DO - 10.19087/jveteriner.2019.20.4.519, 2019)
The aim of the research was to prove the potency of cassava leaf extract to overcome heat stress of adult quails on the variable of antibody titer of Newcastle Disease (ND), MDA level, and total protein. The research was divided into four groups and conducted in 6 replications for each group, consisting of control group, group A, B, and C. All the groups were exposed to heat stress, and then treated with cassava leaf extract with different dosages for 5,292 mg/168 g body weight, 10,584 mg/168 g body weight, and 21,168 mg/168 g body weight for 28 days after being adapted for a week. Variables of antibody titer of Newcastle Disease (ND), MDA level, and total protein were measured every week. The result showed that HI titer of overall tested groups was less than 2 HI units. HI titer contains positive antibody of antibody titer of ND if it reaches 16 HI units. HI test in the present study showed that all of quail serums contained negative antibody of ND. The level of MDA fluctuated with the highest and smallest value was found in group B and control group, respectively. In addition, the administration of cassava leaves extract tended to decrease total protein, where control group was significantly different to both group A and C (P < 0,05). In conclusion, cassava leaves extract has the potential to decrease the stress level, but the administration up to 21,168 mg/168 g BB has not been able to decrease the level of MDA in quails that suffered from heat stress. In Dosage 21, 168 mg extract of cassava leaves was potential to lower stress level so that it was unable to stimulate immune respond to form ND titer antibody.